2012
DOI: 10.1186/1743-7075-9-39
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined maternal administration with alpha-ketoglutarate (AKG) and β-hydroxy-β-methylbutyrate (HMB) on prenatal programming of skeletal properties in the offspring

Abstract: BackgroundNutritional manipulations during fetal growth may induce long-term metabolic effects in postnatal life. The aim of the study was to test whether combined treatment of pregnant sows with alpha-ketoglutarate and β-hydroxy-β-methylbutyrate induces additive long-term effects on skeletal system properties in the offspring.MethodsThe study was performed on 290 pigs obtained from 24 sows divided into 4 equal groups and subjected to experimental treatment during two weeks before delivery. The first group con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 41 publications
8
27
0
Order By: Relevance
“…Meanwhile, higher plasma leucine, glucose, and insulin levels were observed in offspring in the HMB group, which is accordance with the results of Tatara et al [28] and Wan et al [14], and HMB could increase plasma amino acid and glucose levels of pigs [14, 28]. In this respect, insulin, glucose and amino acid were the important anabolic promoters affecting skeletal muscle protein synthesis [24], moreover, no difference were observed in mRNA expressions of MuRF1 and MAFbx , which also provided the further evidence of the similar protein degradation in skeletal muscle of pigs between treatments.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, higher plasma leucine, glucose, and insulin levels were observed in offspring in the HMB group, which is accordance with the results of Tatara et al [28] and Wan et al [14], and HMB could increase plasma amino acid and glucose levels of pigs [14, 28]. In this respect, insulin, glucose and amino acid were the important anabolic promoters affecting skeletal muscle protein synthesis [24], moreover, no difference were observed in mRNA expressions of MuRF1 and MAFbx , which also provided the further evidence of the similar protein degradation in skeletal muscle of pigs between treatments.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, an important observation was that pigs from sows in HMB group had greatly higher finishing BW compared with pigs from sows in the CON group, which was similar with the results of Tatara et al [28, 29], who showed that when sow supplemented daily with 0.05 g/kg BW of HMB-Ca during the last two weeks of gestation, fattening pigs exhibited higher final BW at d 180 of age. Meanwhile, we found no statistical difference in ADFI between treatments from the weaning to d 180 after birth.…”
Section: Discussionsupporting
confidence: 87%
“…Growth hormone (GH) and insulin‐like growth factor 1 (IGF‐1) contribute to somatotrophic axis and play a fundamental role in the regulation of metabolism and growth in animals and humans (Tatara et al., ). Increased GH and IGF‐1 serum levels were found in the offspring of sows receiving HMB during pregnancy (Tatara et al., , ). In neonatal lambs after oral supplementation of HMB during the first 21 days of life, a 70% greater amount of GH and IGF‐1 were reported, with a subsequent decrease below control values at 130 days of life (Tatara, ).…”
Section: Metabolism Of Hmbmentioning
confidence: 99%
“…(), Tatara (), Tatara et al. () on the basis of research performed with pigs and lambs. The authors concluded that HMB‐supplemented animals were significantly heavier at birth showed increased daily weight gain and therefore reached slaughter weight faster than the control group; however, final body weights of control and HMB‐treated groups were similar.…”
Section: Hmb Supplementation Utility In Animalsmentioning
confidence: 99%
“…However, there is recent epigenetic data in animal models to suggest that HMB given during pregnancy can result in prenatal programming of skeletal muscle tissue. Specifically, maternal supplementation of HMB during pregnancy resulted in greater weight and lean mass gain in piglets than those not under maternal treatment [51]. Moreover, research in growing, pre-adolescent rats suggests that HMB supplementation was able to stimulate skeletal muscle hypertrophy in the extensor digitorum longus and soleus muscles [52], and that HMB was able to increase the mTOR and phosphorylation of p70S6K in the EDL muscle [52].…”
Section: Introductionmentioning
confidence: 99%